Functional connectivity-related changes underlying mindfulness meditation for internet gaming disorder: a randomized clinical trial - Xuefeng Xu; Haosen Ni; Huabin Wang; Tongtong Wang; Chang Liu; Xiaolan Song; Guang-Heng Dong (npj Mental Health Research)
Abstract Internet gaming disorder (IGD) is recognized as a mental health issue. Traditional interventions have limitations, but mindfulness meditation (MM) shows promise due to its flexibility and social acceptance. Study 1, fMRI data from 61 IGD patients and 60 healthy controls (HCs) were compared to assess functional connectivity (FC). Study 2- a randomized clinical trial, 80 IGD patients underwent either an MM intervention (twice-weekly for 8 sessions) or progressive muscle relaxation (PMR) as a control (pre-registered-Chinese clinical trial registry, ChiCTR2300075869, September 18, 2023). Study 1 revealed abnormal FC within the executive control network (ECN) and between the ECN and reward network in IGD patients. Study 2 showed that MM enhanced FC within the ECN and frontostriatal pathway. MM refining the coupling between brain regions involved in executive control and reward processing. This enhancement improves top-down control over game craving. These findings suggest that MM can effectively treat IGD.